A CMK-5-encapsulated MoSe2 composite for rechargeable lithium-ion batteries with improved electrochemical performance. Issue 37 (17th August 2017) - Zheng, Cheng; Chen, Congrong; Chen, Lin; Wei, Mingdeng
Abstract : A composite of MoSe2 /CMK-5 was fabricated through a nanocasting route, in which ultra-thin two-dimensional MoSe2 nanosheets were encapsulated in the mesopores of CMK-5, exhibiting improved electrochemical performance for lithium-ion batteries. Abstract : A tubular composite of MoSe2 /CMK-5 was fabricated through a nanocasting route, in which ultra-thin two-dimensional MoSe2 nanosheets were encapsulated in ordered tubular mesoporous carbon CMK-5 with a massive internal surface area. As an anode for Li-ion intercalation, the CMK-5 matrix could not only provide sufficient space to buffer the volume change of MoSe2 during the charge–discharge process, but also increase the electrical conductivity and shorten the lithium-ion diffusion pathway. It was found that the MoSe2 /CMK-5 composite exhibited an outstanding specific capacity of 788 mA h g −1 at a current density of 100 mA g −1 and excellent high rate performance. More importantly, a capacity of 451 mA h g −1 could be retained after 1000 cycles even at a current density as high as 2000 mA g −1, indicating that such a composite has long-term cycling stability.